DEFINING THE ROLE OF THE EU AS A GLOBAL ACTOR: CHALLENGES AND PERSPECTIVES - Vasko Naumovski (Konrad Adenauer Foundation, Republic of North Macedonia / Institute for Democracy “Societas Civilis”, Skopje, 2021)
The Union’s internal cohesion is key to the effectiveness of European responses and dealing with global crises. The EU institutions and the member states must establish a common vision that would be realized through strong coordination structures for harmonization of action and adoption of appropriate measures for increased visibility in the modern international system. The concept of the EU as a global actor that relies primarily on its soft power is a concept that belongs to the past, as it cannot provide a sufficient international presence in proportion to the size of the Union. The EU as a global power with combined power characteristics is a more appropriate concept to achieve the ambitions for influence on the international scene. The COVID-19 crisis has confirmed the thesis that the EU needs “strategic autonomy” to be able to reduce its dependence on other global actors in its foreign relations, so that it can make more autonomous decisions to promote its interests. There are several areas in which the EU has already developed appropriate instruments and initiatives to assert its authority, such as the protection of the environment and climate change, energy and transport, the digitalization process and finance, and needs to work harder to strengthen its position on dealing with modern security and defense threats. In all these areas, the EU’s normative power as a promoter of certain values is the strongest attribute it should use to maintain multilateralism through more visible participation in international organizations. The current crisis brings with it great uncertainty and unpredictability, but what is quite certain is that the map of Europe will not change. Therefore, the EU should recognize the Western Balkans as its ally and partner in the process of the continent’s unification and strengthening. Therefore, the EU should approach the region as an equal actor and include it in its foreign policy initiatives to increase continental integrity and promote common European values.
Keywords: EU, Enlargement, Globalism, Western Balkans